Internacionalização e o desenvolvimento discente : Revelações a partir da autoavaliação do Programa de Pós-Graduação em Enfermagem da UFPB - Costa, Nathali de Oliveira (2024)
This study explores the internationalization actions of the Postgraduate Program in Nursing (PPGENF) of the Federal University of Paraíba (UFPB). The main objective of this research is to analyze how the internationalization practices adopted by the PPGENF contribute to the academic and professional development of students. A descriptive and documentary approach was adopted, investigating the most recent National Postgraduate Plans, the Nursing Area Document, the UFPB Institutional Development Plan and the PPGENF Strategic Plan, in addition to performing content analysis of the PPGENF self-assessment reports from 2019 to 2023. The theoretical basis of the study is based on concepts of formative assessment and internationalization in higher education. The results revealed that the internationalization practices of the PPGENF have potential, such as the presence of foreign professors and the holding of virtual events, which expand students' access to global experiences and knowledge. However, specific weaknesses were identified, including low student participation, difficulties with mastering other languages, and the need for greater institutional support. These challenges reflect a gap between internationalization practices and the educational objectives of the PPGENF, imposing the need for more integrated strategies that consider the perspective of students. It is concluded that internationalization is an essential tool for improving the quality of postgraduate studies, especially in the context of the PPGENF. As products of the research, a technical report was prepared, which offers practical recommendations to improve the internationalization actions of the PPGENF, and a digital booklet with the objective of introducing concepts and guidelines on internationalization at UFPB.